Circulating tumor DNA determining hyperprogressive disease after CAR-T therapy alarms in DLBCL: a case report and literature review - He, Jiajie; Zou, Rui; Kang, Liqing; Yu, Lingzi; Wang, Peng; Shao, Yang; Liang, Junheng; Wu, Depei; Jin, Zhengming; Qu, Changju (Frontiers in Oncology, 2023)
Chimeric antigen receptor T-cell therapy (CAR-T) has been widely applied in the clinical practice of relapse/refractory (R/R) diffuse large B-cell lymphoma (DLBCL) for its promising effects. Hyperprogressive disease (HPD) has gained attention for rapid tumor progression and has become a therapeutic and prognostic challenge. Here, we presented a patient who suffered from several recurrences previously and controlled well with a very small tumor lesion left was infused with CD19/CD22 bispecific CAR-T with no immune effect or cell-associated neurotoxic syndrome or cytokine release syndrome observed. However, rapid deterioration, subsequent imaging examination, circulating tumor DNA and serum biomarkers detection identified HPD. The patient got no response to salvage treatment and died in 40 days after infusion. To our knowledge, only one case of HPD in DLBCL after CAR-T therapy has been reported. This fatal case alarmed the risk of HPD and ctDNA profile monitoring we used was performed as a non-invasive method to diagnose HPD, providing far-reaching practical instruction for CAR-T therapy.